Solvent-dependent recovery characteristic and asphaltene deposition during solvent extraction of heavy oil. (1st March 2020) - Li, Xuesong; Berg, Steffen; Castellanos-Diaz, Orlando; Wiegmann, Andreas; Verlaan, Marco
Abstract: Most traditional recovery methods for heavy oil, such as thermal recovery processes, are energy consuming and greenhouse gas emission is intense. Non-thermal based solvent extraction methods are attractive because they require much less heat, no water and the produced heavy oil has low viscosity even at surface conditions, making it easier to transport. However, heavy oil recovery by solvent occurs mainly at the moving solvent front which is only a few millimetres width. It is thus challenging for it to be modelled in reservoir scale and leaves a large uncertainty regarding the recovery factor prediction. For any reliable scaling up, the fundamental details of the extraction in millimetre range down to the pore scale need to be understood. In this study, we use a 2D micromodel operated at reservoir pressure and temperature conditions, in order to analyse the extraction processes of bitumen by solvent. Two different solvents, pentane and propane, which are both considered as field-relevant candidates, are selected for comparison and toluene is selected as a fully miscible reference case. By imaging both the displacement pattern on a larger scale of 5 cm and, simultaneously, the details of the flow processes at pore scale, it was observed that both pentane and propane precipitate asphaltenes. But in the case of pentane, the precipitated asphaltenes are solid which significantly reduce the permeability thus resulting in plugging. The result from flow simulation confirmed the influence of formation plugging on the flow and diffusion process. In the case of propane, the precipitated asphaltenic phase remains liquid, hence mobile, which leads to capillary trapping. Consequently, the recovery factor for propane is ~15% higher than for pentane and more stable. In general, this study suggests that heavy oil recovery using solvent is a dynamic process where the pore scale phase characteristic of asphaltene has a strong influence both on the transport of fresh solvent and the production of dissolved crude components. These differences between the solvent are key and should be included in field scale estimations.